Modulation of the human electro-cerebellogram (ECeG) during vestibular and optokinetic stimulation. (1st November 2019) - Todd, Neil PM; Govender, Sendhil; Colebatch, James G
Highlights: The human electrocerebellogram (ECeG) exhibits considerable plasticity during vestibular and optokinetic stimulation. Specifically following vestibular stimulation in which a vestibular cerebellar evoked potential (VsCEP) appears there is following pause in the ECeG. Overall during vection with vestibular stimulation there is a reduction in the power of the ECeG but which is accompanied by an increase in cerebro-cerebellar coherence. Both change in ECeG power and change in cerebro-cerebellar coherence correlate with the subjective sensation of vection. The above properties are consistent with a human cerebro-cerebellar network that exhibits the plasticity expected from the known inhibitory properties of Purkinje cells and the pausing of spontaneous Purkinje cell activity following a climbing-fibre evoked response. Abstract: We have recently shown that it is possible to record vestibular cerebellar evoked potentials (VsCEPs) in the form of a contralateral short-latency biphasic positive-negative wave with surface electrodes placed over the posterior fossa and, in parallel with this, the spontaneous electrocerebellogram (or ECeG). VsCEPs were further shown to exhibit considerable plasticity depending on visual context and in this article we show additionally that the ECeG power and cerebro-cerebellar coherence which accompanies the VsCEPs also changes systematically during vestibular and optokinetic stimuli. In a sample of nine healthy human subjects, half of whom had VsCEPs, we recorded in parallel the ECeG and for comparison the EEG from central scalp sites. The results showed that during vection with vestibular stimulation there is actually a reduction in the power of the ECeG accompanied by an increase in cerebro-cerebellar coherence, both of which correlate with the subjective sensation of vection. Only the VsCEPs present group showed the significant power reduction and increase in coherence, indicating a link between the VsCEP and plasticity in the ECeG. We suggest that these data are consistent with a human cerebro-cerebellar network associated with control of the VOR. The network exhibits the plasticity expected from the known inhibitory properties of Purkinje cells and the pausing of spontaneous Purkinje cell activity following a climbing-fibre evoked response with conjunctive inputs from the mossy-fibre system.